2019
DOI: 10.1002/fsn3.1326
|View full text |Cite
|
Sign up to set email alerts
|

Camellia (Camellia oleifera Abel.) seed oil promotes milk fat and protein synthesis‐related gene expression in bovine mammary epithelial cells

Abstract: Camellia (Camellia oleifera Abel.) seed oil is a commonly used edible oil of China. In ancient Chinese literature, it is mentioned to be helpful for postpartum repair and lactation in women. Research on camellia seed oil (CO) as a feed additive for dairy cattle is less. We investigated the effect of CO on the expression of milk fat and protein syntheses-related genes in differentiated bovine mammary epithelial cells (MAC-T) using soybean oil (SO) as the control. The results showed that CO increased the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Breast specific STAT5-knockout mice had impaired development of the mammary gland and the decrease of whey protein content in milk [15]. In the mammary epithelial cell lines of cows [16] and dairy goats [17], STAT5 binds to the CSN2 gene promoter and promotes the transcription and synthesis of β-casein.…”
Section: Introductionmentioning
confidence: 99%
“…Breast specific STAT5-knockout mice had impaired development of the mammary gland and the decrease of whey protein content in milk [15]. In the mammary epithelial cell lines of cows [16] and dairy goats [17], STAT5 binds to the CSN2 gene promoter and promotes the transcription and synthesis of β-casein.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, several natural molecules or derivates has been tested for the treatment of bovine mastitis [ 9 ]. Natural molecules are preferred thanks to their safer use for both the animal and its derivatives [ 10 , 11 , 12 ]. Interesting results have been obtained from antioxidant natural compounds such as baicalein [ 13 ], moringa extract [ 14 ] and curcumin [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…39 Camellia seed oil promotes the CSN2 transcription level, accompanied by the decrease of CSN1S1 mRNA in BMEC. 40 Our previous study revealed that the CSN1S1 gene negatively affected STAT5a activity and β-casein synthesis in GMEC. 17 Here, we performed rescue experiments to confirm whether miR-204-5p/-211 could increase STAT5a phosphorylation and β-casein expression through the CSN1S1 gene.…”
Section: ■ Discussionmentioning
confidence: 94%